Biochemical and computational characterization of laccases involved in bioremediation - PRANITA ROY,; ANUKRITI VERMA,; TANU ALLEN,; BHAWNA RATHI, (International Journal of Pharma and Bio Sciences, 2016)
Laccase (benzenediol: oxygen oxidoreductases; E.C. 1.10.3.2) a copper oxidase enzyme is capable of oxidizing phenolic and non-phenolic lignin related compounds as well as highly recalcitrant environmental pollutants such as aromatic amines. Their broad substrate specificity makes laccases highly suitable for diverse applications such as pulp bleaching, textile dye bleaching and bioremediation, serving as a more environmental friendly alternative than the conventional chemical processes. Its substrate flexibility offers the prospect for screening xenobiotic pollutants in order to predict potential targets for degradation. It is essential to find novel, efficient enzymes to further develop these applications. Isolation and identification of novel laccase producing bacteria becomes essential, because majority of researchers have focused on using fungal laccases. However, bacterial laccases in comparison to fungal laccases exhibits higher pH and temperature tolerance, oxygen limitations, with low redox potential than their fungal orthologs. The present study was thus aimed to screen and biochemically characterize indigenous laccase producing bacterial strains isolated from different sites of Agra canal. Four bacterial strains were selected by screening procedure based on their oxidative activity on tannic acid and ABTS (2, 2'-azinobis (3-ethylbenzthiazoline-6-sulfonate). Detailed biochemical characterization and species identification confirmed the isolates as Acinetobacter boumanii, Escherischia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa. Further the structures of these isolates were predicted and verified for protein-ligand docking analysis against toxic environmental pollutants. This study aided in the prediction of biodegradation of selected pollutants prevalent in water and soil. This work can be utilised further to ï¬nd putative pollutants for other biodegradative enzymes.